Disinfection of Fertile Eggs of Free-Range Poultry with Essential Oils - Nogueira,Wedson Carlos Lima (2019)
SUMMARY The effect of the disinfection of fertile eggs of free-range poultry with essential oils from Cymbopogon flexuosus and Lippia rotundifolia was evaluated. The treatments applied to the eggs were (v v-1): 1% essential oil from C. flexuosus (CF), 1% essential oil from L. rotundifolia(LR), 0.1% CF + LR, and 0.1% quaternary ammonia (QA) (positive control). The eggs were incubated for 21 days, the birds from hatched eggs were counted and weighed, and not hatched eggs were opened and examined macroscopically to determine egg fertility, and embryonic death time. The antimicrobial action of the essential oils was determined through quantitative analyses, considering aerobic mesophylls, filamentous fungi, yeasts, and total coliforms. Mortality was high in the treatments, especially in the treatment with essential oil from C. flexuosus. The highest hatchability was found in the treatment with QA. The treatments with singly or combined essential oils were more efficient in decreasing microbial count than QA. The essential oils from C. flexuosus and L. rotundifolia reduced the microbial load of fertile eggs of the free-range poultry evaluated.